Prediabetes is not a risk factor for subclinical coronary atherosclerosis. (15th September 2017) - Park, Gyung-Min; Cho, Young-Rak; Lee, Seung-Whan; Yun, Sung-Cheol; Won, Ki-Bum; Ann, Soe Hee; Kim, Yong-Giun; Kim, Shin-Jae; Roh, Jae-Hyung; Kim, Young-Hak; Yang, Dong Hyun; Kang, Joon-Won; et al.
Abstract: Background: There are limited data regarding the influence of glycemic status on the risk of subclinical coronary atherosclerosis on coronary computed tomographic angiography (CCTA) in asymptomatic individuals. Methods: We analyzed 6434 asymptomatic individuals who underwent CCTA. The degree and extent of subclinical coronary atherosclerosis were assessed by CCTA, and ≥ 50% diameter stenosis was defined as significant. Of study participants, 2197 (34.1%), 3122 (48.5%), and 1115 (17.3%) were categorized as normal, prediabetic and diabetic individuals, respectively. Results: Compared with normal individuals, there were no statistically differences in the adjusted odds ratios of prediabetic individuals for significant coronary artery stenosis (0.98, 95% confidence interval [CI] 0.80–1.22, p = 0.888), any plaque (0.96, 95% CI 0.86–1.07, p = 0.483), calcified plaque (0.90, 95% CI 0.79–1.01, p = 0.080), non-calcified plaque (1.02, 95% CI 0.88–1.17, p = 0.803), and mixed plaque (1.00, 95% CI 0.82–1.22, p = 0.983). However, adjusted odds ratios for significant coronary artery stenosis (1.71, 95% CI 1.34–2.19, p < 0.001), any plaque (1.45, 95% CI 1.26–1.68, p < 0.001), calcified plaque (1.35, 95% CI 1.15–1.57, p < 0.001), non-calcified plaque (1.33, 95% CI 1.11–1.59, p = 0.002), and mixed plaque (1.64, 95% CI 1.30–2.07, p < 0.001) of diabetic individuals were significantly higher than those of the normal individuals. Conclusion: In asymptomatic individuals, diabetic individuals had a higher risk for subclinical coronary atherosclerosis, but prediabetic individuals were not associated with an increased risk of subclinical coronary atherosclerosis. Highlights: Prediabetes is not a risk factor for subclinical coronary atherosclerosis. Diabetes is an independent risk factor for subclinical coronary atherosclerosis. In prediabetic individuals, concomitant cardiac risk factors are corrected. In diabetic individuals, efforts for glucose control are required.